Plant community and diversity in a privately-owned multi-story agroforest in Mindanao, Philippines - MARION JOHN MICHAEL M. ACHONDO; AARON FROILAN M. RAGANAS; MARIA VICTORIA O. ESPALDON (Society for Indonesian Biodiversity, 2026)
Abstract. Achondo MJMM, Raganas AFM, Espaldon MVO. 2026. Plant community and diversity in a privately-owned multi-story agroforest in Mindanao, Philippines. Biodiversitas 27 (4): d270406. https://doi.org/10.13057/biodiv/d270406. The lower slopes of Mt. Kitanglad Natural Park in Bukidnon, Mindanao, are increasingly dominated by monoculture plantations that threaten native biodiversity. The Binahon Agroforestry Farm (BAFF), a privately managed multi-strata agroforest, represents an alternative land-use model that integrates production and ecological stewardship. This study assessed the plant community composition, diversity, and structure of BAFF using 34 quadrats with size 20 m × 20 m each (total sampling area = 13,600 m²) and 800 m of transect sampling. A total of 165 plant species belonging to 65 families were recorded, with Fabaceae, Moraceae, Asteraceae, Euphorbiaceae, and Myrtaceae as the most represented families. Trees (67 species) were the dominant growth form, followed by herbs (35) and shrubs (33). Nine endemic (5.5%) and nine threatened species (5.5%) were documented, highlighting the ecological value of the site. The Shannon-Wiener index (H′ = 4.08) and Pielou’s evenness index (J = 0.80) indicated a diverse and almost balanced plant community, falling within the range reported for secondary forest ecosystems in previous studies in Mindanao. Species with the highest importance values were Pinus kesiya, Acacia mangium, Eucalyptus sp., Rubroshorea negrosensis, and Vitex parviflora. The coexistence of native, endemic, and cultivated species suggests a structurally heterogeneous vegetation that promotes ecological functions within a managed landscape. Overall, the findings indicate that well-managed agroforests such as BAFF may serve as valuable components of landscape-level conservation, supporting biodiversity within productive land-use systems and potentially informing agroforestry-based planning and policy in Mindanao.